Indexing Morality: Ritual Language and the Construction of Moral Identity in the Katoba Ceremony - Ela Martisa; Harlina Sahib; Ayyub Khan (IAHN-TP Palangka Raya, 2026)
This study examines how ritual language functions as a semiotic mechanism for constructing moral identity in the Katoba ceremony in Southeast Sulawesi. While previous research has explored language and morality, localized ritual practices in non-Western contexts remain underrepresented. To address this gap, this study adopts a qualitative, discourse-based approach grounded in semiotic theory, indexicality, and Systemic Functional Linguistics to analyze selected ritual utterances. The findings show that moral identity is constructed through recurring linguistic patterns that index coherence between belief, speech, and action. Triadic expressions linking heart, tongue, and behavior serve as key structures in defining moral personhood. In addition, ritual language encodes moral transformation through structured stages of repentance, establishes ethical boundaries through distinctions between lawful and unlawful conduct, and reinforces hierarchical social relations, particularly within the family. These linguistic forms operate not only as representations but also as performative and indexical signs that actively shape moral understanding and social positioning. The study demonstrates that moral identity in the Katoba ritual emerges dynamically through participation in culturally embedded discourse, reflecting the interaction between religious values and local linguistic practices